Analysis of the Transition of the 2013 Curriculum to the Independent Learning Curriculum - Sherina Purbo Laras; Felizhia Ceccile Aundrea; Zaneti Amelia; Suparmi (Aslim: Journal of Education and Islamic Studies, 2024)
This research aims to find out the comparison of the K13 curriculum and the Merdeka Curriculum by looking for the advantages and disadvantages of each curriculum. This research uses a literature study method to explore information about the K13 Curriculum and the Merdeka Curriculum, especially those related to the advantages and disadvantages of these curricula to find out the comparison between the K13 curriculum and the Merdeka Curriculum. The results of this research indicate that curriculum changes are a challenge for teachers in implementing new strategies in the curriculum used. Even though it is a challenge for teachers to implement new strategies, the independent curriculum is still superior to the 2013 curriculum. The independent curriculum prioritizes character building of students through developing Pancasila student profile projects.